Representasi Pertemanan Toxic dalam Perspektif Interaksionisme Simbolik (Studi pada Mahasiswa di Kota Malang) - Sefia Tripramesti; Luluk Dwi Kumalasari (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Toxic friendships among university students are a social phenomenon shaped by symbols and interpretations. This study aims to explore how social symbols are produced, interpreted, and used in the interactions of toxic friendships among students in Malang City. A qualitative approach with a phenomenological method was employed to examine students’ subjective experiences. George Herbert Mead’s theory of symbolic interactionism was adopted as the analytical framework, which emphasizes that meaning emerges through social interaction and individual interpretation. Data were collected through in-depth interviews, focus group discussions (FGDs), and participatory observations with students from various universities in Malang. The findings reveal that verbal symbols such as sarcasm, mockery, and ridicule, along with non-verbal symbols such as gaze, gestures, and selective ignoring, play a significant role in shaping toxic patterns of interaction. Students’ interpretations of these symbols are often driven by the desire to maintain group membership and pseudo-solidarity, which perpetuates the toxic dynamics. This study affirms that toxic friendships are a social construction sustained through symbols and interpretations, while also demonstrating the relevance of Mead’s symbolic interactionism in understanding the dynamics of student friendships.